(3GdJhVjM dTQM GdLGeY GdUMjMs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s; (3eMeO Hf ESeGYjd Hf EHQGgje Hf GdeZjQI GdHNGQj, CHh YHO Gddg,J (B256 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH GdONhd Ydi GdejJ EPG COQL s
(3BNQgG (B:s
(3hjfJgi HHGH bhdg Udi Gddg Ydjg hSde (B:(3W EPG JhVC adjSJfTb (B" (3ef cJGH GdUhe s
(3GdfSNI HgG MhGTs
(3LRA BNQ efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B71 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs